KEBERLANGSUNGAN HUTAN ADAT IMBO PUTUIH KENEGARAIAN PETAPAHAN KABUPATEN KAMPAR PASCA PENGAKUAN NEGARA - Nasari, Irma; Marta, Auradian Marta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The Imbo Putui Traditional Forest of Kenegerian Petapahan, Tapung District, Kampar Regency, Province has been recognized by the state through a Decree issued by the Ministry of Environment and Forestry Number: 7503/MENLHK PSKL/PKTHA/KUM.1/9/2019 and Kampar Regent Decree Number: : 660-491/X/2018. Which was handed over directly by the President of the Republic of Indonesia, Mr. Joko Widodo, at the Sultan Syarif Hasyim Forest Park, Siak Regency. The purpose of this research is to find out how the sustainability of the Imbo Putui Indigenous Forest is after the issuance of Decree (SK) Number 7503/MENLHK-PSKL/PKTHA/KUM.1/9/2019 issued by the Indonesian Ministry of Environment and Forestry, and the decision Kampar Regent Number: 660-491/X/2018. The method used in this research is qualitative, with a literature review approach, observation and interviews. The results of this study indicate that there have been many changes in both the level of interaction and communication between the village government and traditional institutions for the better, the forest has become a place to increase income for residents, the forest has also become a place for ecotourism, in terms of the economic sector, the historical sector, and the ecotourism sector. Keywords : Forest, Recognition, Sustainability, Imbo Putui, indigenous peopl